2017
DOI: 10.3892/etm.2017.4454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of salmon nasal proteoglycan on biomarkers for cartilage metabolism in individuals with knee joint discomfort: A randomized double-blind placebo-controlled clinical study

Abstract: A randomized double-blind placebo-controlled clinical trial was conducted to evaluate the chondroprotective action of salmon nasal cartilage proteoglycan on joint health. The effect of oral administration of proteoglycan (10 mg/day) on cartilage metabolism was evaluated in individuals with knee joint discomfort but without diagnosis of knee osteoarthritis. The average age of patients was 52.6±1.1 years old. The effect of proteoglycan was evaluated by analyzing markers for type II collagen degradation (C1,2C) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Of note, changes to baseline resting values of COMP were not associated with loading changes over time, suggesting that the mechanical stimulus‐response model, 37 wherein the moderate 30‐minute walk was used to elicit a response in COMP, may enhance the utility of COMP as a biological treatment indicator. Baseline resting values of COMP in this study were similar to those reported in the literature in knee OA utilizing the same ELISA Kit 38,39 . Further this study indicated the KAM during gait is a potential important metric for stimulating the COMP response.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Of note, changes to baseline resting values of COMP were not associated with loading changes over time, suggesting that the mechanical stimulus‐response model, 37 wherein the moderate 30‐minute walk was used to elicit a response in COMP, may enhance the utility of COMP as a biological treatment indicator. Baseline resting values of COMP in this study were similar to those reported in the literature in knee OA utilizing the same ELISA Kit 38,39 . Further this study indicated the KAM during gait is a potential important metric for stimulating the COMP response.…”
Section: Discussionsupporting
confidence: 86%
“…Baseline resting values of COMP in this study were similar to those reported in the literature in knee OA utilizing the same ELISA Kit. 38,39 Further this study indicated the KAM during gait is a potential important metric for stimulating the COMP response. Taken together with the finding that the first peak of the KAM 18,19 and the KAM impulse 30 have been related to OA disease progression, the association found in this study provides a possible mechanistic explanation for the benefit of load reduction.…”
Section: Discussionmentioning
confidence: 65%
“…For example, several bioactive compounds can be isolated from processing waste of shrimps, one of the most widely consumed seafoods, including chito-oligosaccharides from chitin, astaxanthin a red carotenoid with high antioxidant capacity, and Ω-3 polyunsaturated fatty acids [164][165][166]. Salmon nasal cartilage is a valuable source of bioactive proteoglycans reported for anti-angiogenic activity, relieving joint pain discomfort in elderly people and promoting wound healing [167][168][169]177]. Fish skin is also an important source of collagen that can be hydrolysed to bioactive peptides with multiple health benefits with antioxidant, anti-hypertensive, and anti-diabetic activities, as well as enhancing learning and memory [170][171][172].…”
Section: Fish and Shellfish Wastementioning
confidence: 99%
“…In practice, this unique approach has been explored in specific clinical areas such as rheumatology and skin aging. In a clinical trial on males and females with severe knee pain, oral salmon nasal proteoglycans have been proved to be effective in decreasing collagen degradation and promoting collagen synthesis [95]. As a therapy for skin aging, a marine-based proteoglycan complex significantly improved skin viscoelasticity and reduced the number of wrinkles and skin looseness in both men and women [96].…”
Section: Proteoglycan-based Therapies For Hair Lossmentioning
confidence: 99%
“…Further exploration revealed that close to half of the proteoglycan absorption in the jejunum and the ileum is via clathrin-mediated endocytosis [116]. Furthermore, since bioactivity depends on sufficient bioavailability and bioaccessibility, positive outcomes produced by oral PRT with Nourkrin ® in clinical trials in a variety of health conditions [95,[99][100][101]117] may be taken as indirect evidence for oral bioavailability of specific proteoglycans. However, making reliable conclusions would require direct in vivo pharmacokinetic studies.…”
Section: Pharmacology Of Oral Prtmentioning
confidence: 99%